Did Vasco da Gama matter for European markets? - O'Rourke, K; Williamson, J (Blackwell Publishing, 2009)
This article explores the impact of the ‘Voyages of Discovery’ on European spice markets, asking whether the exploits of Vasco da Gama and others brought European and Asian spice markets closer together. To this end we compare trends in pepper and fine spice prices before and after 1503, the year when da Gama returned from his financially successful second voyage. Other authors have examined trends in nominal spice prices, but this article uses relative spice prices, that is, accounting for inflation. We find that the Voyages of Discovery had a major impact on European spice markets, and provide a simple model of monopoly and oligopoly to decompose the sources of the Cape route's impact on European markets. Finally, we offer some speculations regarding the impact of the Cape route on intra-European market integration.